Peran Mataf (Penjaga Mamar) Manufua di Desa Sillu Kecamatan Fatuleu - Albert Malafu; Marthen Dillak; Agustin L. M. Rohi Riwu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The role of Mataf (Mamar Guardians) Manufua in Sillu Village, Fatuleu District is a problem that impacts various aspects including customs and governance, legal certainty, and social stability of the local community, as well as mamar ownership. In this context, the role of mataf is very important to ensure comfort for mamar owners. This study was conducted based on the consideration that the role of mataf in Sillu Village has almost disappeared, causing misuse in utilizing natural resources from mamar that are not by their owners. In addition, this study was conducted to build the potential of human resources in Sillu Village in understanding the importance of the role of mataf in maintaining mamar. Based on the description above, the role of mataf in maintaining mamar needs to be studied using empirical legal research. The main problem in this study is how the role of mataf guards mamar Manufua in Sillu Village, Fatuleu District. Data collection techniques used were observation, interviews and literature studies. The results of the study indicate that the role of mataf in maintaining mamar in Sillu Village, Fatuleu District is quite good with the presence of guarding from mataf. Mataf are able to provide information on various events occurring within the mamar area, from harvesting mamar crops, irrigation of mamar fields, security, and collecting scattered mamar crops in one location so that mamar owners can easily identify them when collecting their Manufua mamar crops. The results of this study indicate a positive role or positive outcomes of the mataf's role in safeguarding mamar. Therefore, it is recommended that students, especially university students, or scientists, further study the potential role of mataf in a broader context.